Online advertisement: how are visual strategies affected by the distance and the animation of banners? - Pasqualotti, Léa; Baccino, Thierry (Frontiers in Psychology, 2014)
Most of studies about online advertisements have indicated that they have a negative impact on users’ cognitive processes, especially when they include colourful or animated banners and when they are close to the text to be read. In the present study we assessed the effects of two advertisements features - distance from the text and the animation - on visual strategies during a word-search task and a reading-for-comprehension task using Web-like pages. We hypothesised that the closer the advertisement was to the target text, the more cognitive processing difficulties it would cause. We also hypothesised that 1) animated banners would be more disruptive than static advertisements and 2) banners would have more effect on word-search performance than reading-for-comprehension performance. We used an automatic classifier to assess variations in use of Scanning and Reading visual strategies during task performance. The results showed that the effect of dynamic and static advertisements on visual strategies varies according to the task. Fixation duration indicated that the closest advertisements slowed down information processing but there was no difference between the intermediate (40 pixel) and far (80 pixel) distance conditions. Our findings suggest that advertisements have a negative impact on users’ performance mostly when a lots of cognitive resources are required as for reading-for-comprehension.